2007
DOI: 10.2174/157340407781387690
|View full text |Cite
|
Sign up to set email alerts
|

Growth Restriction: Etiology, Maternal and Neonatal Outcome. A Review

Abstract: Intrauterine growth restriction (IUGR) is an important clinical problem associated with increased perinatal mortality and morbidity. The most preferred small for gestational age (SGA) definition is birth weight below the 10th percentile, adjusted for gestational age. The incidence of IUGR is about 4 to 7 %. A variety of hormones are involved. IUGR may be due to chromosomal defects, smoking, early-onset preeclampsia (< 34 weeks), connective tissue and inflammatory rheumatic diseases, maternal infections, severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 213 publications
(268 reference statements)
1
10
0
2
Order By: Relevance
“…Similar results for the values of erythrocytes, he moglobin and ferritin were found in other studies (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results for the values of erythrocytes, he moglobin and ferritin were found in other studies (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 90%
“…Smoking exposure may reduce mean birth weight, and increase the risk of PTD and intrauterine growth restriction (Asmussen and Kjeldsen, 1975; Asmussen, 1977;, Nilsen et al, 1984; Ronco et al, 2005; Goldenberg and Culhane, 2007; Haram et al, 2007). Part of the effect of smoking on birth outcomes may be due to the metabolism of the tobacco compound PAH (polycyclic aromatic hydrocarbons) (Perera et al, 2005; Tsui et al, 2008; Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This well confirmed by a number of retrospective studies which have also demonstrated that the increase in serum ferritin level is associated with the higher risk of SGA in pregnancies with beta thalassemia intermedia (Gaspar, Ortega, & Moreiras, 1993;Origa et al, 2010;Uberos, 2000;Višnjevac, Segedi, Ćurčić, Višnjevac, & Stajić, 2011). Pregnancies complicated by IUGR have higher serum ferritin level due to decrease in ferritin and iron absorption by placenta (Bashiri, Burstein, Sheiner, & Mazor, 2003;Cogswell, Parvanta, Ickes, Yip, & Brittenham, 2003;Ćujić D, 2011;Haram, Svendsen, & Myking, 2007;Ronnenberg et al, 2004;Uberos, 2000).…”
Section: Discussionmentioning
confidence: 76%